Biography of Things – A Ball - Zalewska-Meler, Agnieszka Anita (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The presented text is a study of interest in ball as an element of formation and perception of childhood. The research project was embedded in the paradigm of qualitative, interpretative research, where the focus was on the language of the preschooler, which becomes a reflection of the world of physical culture present in the mind of the child – the narrator. The problem of research is focused on the question: To what extent is the ball and its meanings an element of material culture located in the area of physical culture, and in what circumstances is it a determinant of child-specific pre-school folklore? The resulting space of the presented analyzes is an element of the phenomenographic method, where the use of a partially structured interview with preschool children (N = 80) provided the basis for the analysis of the perception and use of a ball in the cognitive theory of a child’s language space. The main conclusions from the research are: 1) for younger children, the ball is more often an attribute of spontaneous play than conventional actions (governed by rules and patterns), 2) for 5- and 6-year-olds, the ball is an artifact of attractive motor activity, training complex motor skills and competition. In middle childhood, the ball is a domain of spontaneous emotionality and an attribute of children’s play, which becomes a material for perceiving, interpreting and situating oneself in a specific culture of movement. The research was conducted in ten municipal kindergartens in the city of Slupsk, Poland in 2016–2019.